Pathological aspects of poisoning by Crotalaria spectabilis (Fabaceae) seeds in swine. - Souza, A. C. (1997)
A feeding experiment was undertaken using 24 weanling pigs, distributed in four treatments, with 6 animals in each group. The animals of group 1, 2, 3 and 4 were fed with rations containing 0.0, 0.2, 0.4 and 0.6% of Crotalaria spectabilis seeds, respectively, during a period of 90 days. Postmorten examination was performed immediately after death in the animals which died during the experiment. The pigs which survived were sacrificed on the last day of the experiment. During the autopsy fragments of liver, kidneys, lungs and stomach were collected for histological examination. The main clinical signs of the intoxication were subcutaneous oedema, affecting particulary the face, limbs and neck, pale ocular and oral mucous membranes, ruffled bristle, emaciation and apathy. Hydropericardium was the most common finding at necropsy, occurring in several intoxicated animals. The major microscopic changes were fibrosis, bile ductulus proliferation and megalocytosis in the liver, bronchopneumonia and chronic bronchitis, renal tubular cell megalocytosis, nephrosis and chronic nephritis, as well as gastritis and gastric ulcerations. The experimental findings showed that rations contaminated with C. spectabilis seeds, at the used rate, were toxic to swine.